2018
DOI: 10.1017/s0959270918000175
|View full text |Cite
|
Sign up to set email alerts
|

Important Bird and Biodiversity Areas (IBAs): their impact on conservation policy, advocacy and action

Abstract: SummaryBirdLife International´s Important Bird and Biodiversity Areas (IBA) Programme has identified, documented and mapped over 13,000 sites of international importance for birds. IBAs have been influential with governments, multilateral agreements, businesses and others in: (1) informing governments’ efforts to expand protected area networks (in particular to meet their commitments through the Convention on Biological Diversity); (2) supporting the identification of Ecologically or Biologically Significant A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Few attempts, however, have been made to align methodologies across taxa and regions, by having a standardized protocol based on global criteria. The method proposed here was able to identify key at‐sea areas that are a major priority for marine conservation at a global scale (Donald et al., in press). We have shown that the methodology for identifying marine IBAs based on tracking data (Lascelles et al., ) can be easily adapted to meet the specific characteristics of the movement of different taxa, providing a robust framework to identify hotspots for multiple species, a fundamental step in the conservation planning processes (Lascelles, Langham, Ronconi, & Reid, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few attempts, however, have been made to align methodologies across taxa and regions, by having a standardized protocol based on global criteria. The method proposed here was able to identify key at‐sea areas that are a major priority for marine conservation at a global scale (Donald et al., in press). We have shown that the methodology for identifying marine IBAs based on tracking data (Lascelles et al., ) can be easily adapted to meet the specific characteristics of the movement of different taxa, providing a robust framework to identify hotspots for multiple species, a fundamental step in the conservation planning processes (Lascelles, Langham, Ronconi, & Reid, ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, more than 12,000 IBAs have been documented and delineated worldwide, of which ca. 2,600 have been recognized because of the seabird populations they contain (Donald et al., in press). The delimitation of IBAs was initially focused on terrestrial sites and only began to consider IBAs in marine areas as recently as 2004.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are aware that protected areas may not be the only solution for all the challenges that freshwater rivers and its biodiversity face and that other conservation options may need to be employed. For example, BirdLife International´s Important Bird and Biodiversity Areas (IBAs) are a strategy to link policy and local engagement to bird conservation (Waliczky et al 2019). However, at the global scale, IBAs inside protected areas are in better condition, with lower pressures, than those outside protected areas (Butchart et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, at the global scale, IBAs inside protected areas are in better condition, with lower pressures, than those outside protected areas (Butchart et al 2012). In order to have a successful conservation programme, protected areas are a central pillar, but other considerations should also be taken into account, such as economic, sociocultural, political, and enforcement components (Flores Bedregal et al 2015, Waliczky et al 2019.…”
Section: Discussionmentioning
confidence: 99%